Introducing the new culture section of BJPsych Bulletin. (February 2021) - Foreman, David
Summary: This editorial launches the new culture section in the journal. Without any unchallengeable definition of 'culture', potential contributors may consider submissions under four headings: the arts and humanities relating to practice; regulatory culture; becoming a cultured practitioner; and psychiatry's cultural context. A new article type, 'Cultural reflections', has been created, and submissions may reflect any appropriate methodology, including those from the arts. Peer review (from methodologies outside psychiatry if appropriate) will assure quality. Our objectives are to establish BJPsych Bulletin as the 'journal of record' for cultural studies relevant to psychiatric service delivery and demonstrate equivalent quality between them and scientific studies.